Effect of combining attribute and goal framing within messages to change vaccination behavior. (March 2015) - Haydarov, Rustam; Gordon, Joye C.
Abstract : This study examines how presentation of immunization information in a positive or a negative light – also known as message framing – alters attitudes and behaviors associated with parental decisions to vaccinate children. Specifically, the efficacy of attribute frames (characteristics of the vaccine itself) and goal frames (characteristics of outcomes) within a single preventive health messages were questioned using a field experiment employing a 2 (±attribute frame) × 2 (±goal frame) × 2 (high/low involvement) design. Four hundred and seventy-six adult female participants were exposed online to one of four experimental message manipulations or a control condition. The main effect, consistent with previous research implications, found that the combination of the positive attribute frame and the negative goal frame was the only condition that was significantly more persuasive than the control condition. Participants who had children or were pregnant, for whom vaccination was more relevant and meaningful, did not react to message framing differently. However, general pre-existing attitudes toward vaccines, perception of vaccine safety, perceptions of vaccine efficacy, vaccine dread, and vicarious experiences with vaccine side effects were associated with antecedents of vaccination behavior. Overall, this study's methodology emphasizing ecological validity contributes to the evidenced-based applicability of framing theory within the context of health communication.